2010
DOI: 10.1016/j.imlet.2009.12.001
|View full text |Cite
|
Sign up to set email alerts
|

IgG antibodies produced during subcutaneous allergen immunotherapy mediate inhibition of basophil activation via a mechanism involving both FcγRIIA and FcγRIIB

Abstract: 1. Summary The majority of human subjects who receive subcutaneous allergen immunotherapy (IT) develop decreased sensitivity to their allergens. Multiple factors may explain the efficacy of IT, some evidence supports a role for allergen specific IgG antibodies. There is controversy whether such antibodies act by blocking allergen binding to IgE or initiation of active inhibitory signaling through low affinity IgG receptors (FcγRIIB) on mast cells and basophils. In this study, we addressed this question using p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
68
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(69 citation statements)
references
References 36 publications
(43 reference statements)
1
68
0
Order By: Relevance
“…Thirdly, the regulation of PUTGA-specific Th2 responses may also result in downstream regulation of IgE and induction of blocking IgG antibody responses to known TG allergens, a hallmark of specific immunotherapy (SIT) treatment (27,28). Finally, induction of PUTGA-specific Th1 or Treg cells may lead to PUTGA-specific IgG production, which may interfere with IgE-induced mediator release and other immediate-type reactions by mechanisms such as steric hindrance, competition for antigen binding, and inhibitory signaling through FcγRIIB (29,30). Overall, our data suggest that the PUTGAs described in this work could present promising targets for a T-cell-focused specific immunotherapy, which could be safe for administration to higher-risk patients such as asthmatics.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, the regulation of PUTGA-specific Th2 responses may also result in downstream regulation of IgE and induction of blocking IgG antibody responses to known TG allergens, a hallmark of specific immunotherapy (SIT) treatment (27,28). Finally, induction of PUTGA-specific Th1 or Treg cells may lead to PUTGA-specific IgG production, which may interfere with IgE-induced mediator release and other immediate-type reactions by mechanisms such as steric hindrance, competition for antigen binding, and inhibitory signaling through FcγRIIB (29,30). Overall, our data suggest that the PUTGAs described in this work could present promising targets for a T-cell-focused specific immunotherapy, which could be safe for administration to higher-risk patients such as asthmatics.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting this in vivo observation, IgG anti-allergen Abs were reported to inhibit allergen-induced basophil activation (20,59). With this system, Cady et al (20) found that FcgRIIA was required for inhibition. We could not confirm a contribution of FcgRIIA in our experimental setting.…”
Section: Discussionmentioning
confidence: 87%
“…Immune complexes made of allergen and autologous Abs improved allergy to grass pollen (58). Supporting this in vivo observation, IgG anti-allergen Abs were reported to inhibit allergen-induced basophil activation (20,59). With this system, Cady et al (20) found that FcgRIIA was required for inhibition.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations